LOCALIZATION OF NON-HODGKIN LYMPHOMAS IN CHILDREN - Isroil Sh. Adizov; Lola Dj. Sultanova; Bakhtiyor Z. Khamdamov (Central Asian Journal of Medicine, 2023)
Non-Hodgkin's lymphomas are a heterogeneous group of diseases that develop due to malignant monoclonal proliferation of lymphoid cells in the lymphoreticular tissue in the lymph nodes, bone marrow, spleen, liver and gastrointestinal tract. The most common symptom is peripheral lymphadenopathy. However, there are cases without lymphadenopathy, with the presence of circulating atypical lymphocytes. At the time of detection, the disease is likely to be disseminated, and the diagnosis is usually based on a biopsy of the lymph node or bone marrow, or both.